2008
DOI: 10.1158/0008-5472.can-07-2307
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Blockade of Integrin αvβ6 Inhibits Tumor Progression In vivo by a Transforming Growth Factor-β–Regulated Mechanism

Abstract: The A v B 6 integrin is up-regulated on epithelial malignancies and has been implicated in various aspects of cancer progression. Immunohistochemical analysis of A v B 6 expression in 10 human tumor types showed increased expression relative to normal tissues. Squamous carcinomas of the cervix, skin, esophagus, and head and neck exhibited the highest frequency of expression, with positive immunostaining in 92% (n = 46), 84% (n = 49), 68% (n = 56), and 64% (n = 100) of cases, respectively. We studied the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
122
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 55 publications
8
122
0
Order By: Relevance
“…This observation is in accordance with various studies that have reported the role of integrin β 6 in mediating metastasis 15, 34, 35. However, as indicated on the graph (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in accordance with various studies that have reported the role of integrin β 6 in mediating metastasis 15, 34, 35. However, as indicated on the graph (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that avh6 is an attractive tumor target, and several studies have now inhibited tumor growth successfully in vivo using treatments directed against the integrin (33,34). Surprisingly, inhibition of avh6 had no effect on NTGli1 cell Transwell invasion (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…A more fruitful approach may be to target proteins with a more restricted tissue expression profile than that of the TGF-b receptors, which might affect the TGF-b activity only in specific cells of the TME such as in DCs, NK cells, MDSCs and/or T cells. Integrins that activate TGF-b have been considered as such drug targets (Van Aarsen et al 2008;Dutta et al 2014). Another example is GARP, which is required for activation of latent TGF-b on Tregs and platelets (Stockis et al 2009;Tran et al 2009).…”
Section: Future Directions With Tgf-b Blockadementioning
confidence: 99%
“…This antibody may therefore impose a more specific TGF-b blockade immunotherapy for cancer, probably with fewer side effects than blocking TGF-b receptors or ligands, because of the restricted pattern of GARP expression. Other TGF-b modulatory drugs are in development for various disease applications including oncology (Van Aarsen et al 2008;Henderson et al 2013;Salvo et al 2014).…”
Section: Future Directions With Tgf-b Blockadementioning
confidence: 99%